Experimental and exergy evaluation of a PCM integrated active indirect solar dryer for Turkey berries with economic and environmental assessment - K. Senthil Kumar; R. Vasanthi; Mahdi Sh. Jaafar; Arunkumar Munimathan; Manoj Kumar Shanmugam; Mamdooh Alwetaishi; Asif Afzal; Parvathy Rajendran; It Ee Lee (Scientific Reports)
Abstract The research was investigated Turkey Berries drying capability using Active Mode Indirect Solar Dryers at Kovaipudur in Coimbatore, India. The conic-shaped Thermal Energy Storage (TES) covered the solar collector selectively and photovoltaic (PV) panels used to power divergent ducts equipped with DC blowers to enhance the AMISD. An energy analysis revealed meaningful distinctions between the AMISD systems equipped with TES and those operated without TES. The implementation of Thermal Energy Storage brought about a 89.6% collector efficiency rate that exceeded the results commonly reported in related PCM-based solar drying platforms. The proposed combination of a conic-shaped PCM module and a PV-powered diverging duct serves as the main cause behind this performance gain by supporting heat retention and enhancing airflow distribution. The solar dryers achieved better overall efficiency when using TES because they reached 15.23% efficiency compared to 14.8% without TES. The TES system increased the Energy Utilization Ratio up to 29.31 from its initial value of 28. Without TES AMISD used 1384 W of energy but with the implementation of TES it only needed 1268 W to function properly. The information about energy output demonstrates TES produces maximum energy consumption efficiency both with and without Phase Change Material (PCM). The PCM integration in the Specific Collector Area (SAC) improved its energy efficiency from 6.84 to 7.1%. The Sustainability Index scores achieved 8.1 when PCM was included in the experiments while the baseline scores remained at 8.01 without PCM application. Regardless of positive findings the actual experimental data fell short of projecting greenhouse dryer service expectancy to last for 35 years. The study demonstrates that using AMISD with PCM works effectively with improved energy performance while diminishing environmental influence and decreasing operational costs. Based on present circumstances in the region Turkey Berries drying with these specifications appears feasible and sustainable.